1996
DOI: 10.1038/bjc.1996.236
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of the c-kit proto-oncogene product in human malignant and non-malignant breast tissues

Abstract: Summary The immunohistochemical expression of c-kit proto-oncogene product in 57 breast cancer tissues was studied using anti-c-kit proto-oncogene product antibody in comparison with 20 normal breast tissues and 58 benign breast tumours. In normal breast tissues, the c-kit proto-oncogene product was strongly expressed on cell membrane and/or cytoplasm of alveolar and ductal cells. The immunoreactive score (IRS) of c-kit protooncogene product in normal mammary epithelia was 6.22 + 2.11 (mean + s.d.). In benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
2
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 9 publications
5
84
2
4
Order By: Relevance
“…In the present study, a univariate analysis demonstrated the prognosis of the patients with a loss of the c-kit expression to be significantly worse than those with a positive c-kit expression, while a multivariate analysis demonstrated lymph node metastasis and a proliferative activity determined by MIB-1 counts, but not the c-kit expression, to be independently significant prognostic factors for DFS. There was a close correlation between a loss of the c-kit expression and lymph node metastasis in the present study, while no significant correlation between the c-kit expression and lymph node metastasis was found in other studies (Chui et al, 1996;Simon et al, 2004;Ulivi et al, 2004). In the present study, the c-kit expression did not correlate with the MIB-1 counts.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In the present study, a univariate analysis demonstrated the prognosis of the patients with a loss of the c-kit expression to be significantly worse than those with a positive c-kit expression, while a multivariate analysis demonstrated lymph node metastasis and a proliferative activity determined by MIB-1 counts, but not the c-kit expression, to be independently significant prognostic factors for DFS. There was a close correlation between a loss of the c-kit expression and lymph node metastasis in the present study, while no significant correlation between the c-kit expression and lymph node metastasis was found in other studies (Chui et al, 1996;Simon et al, 2004;Ulivi et al, 2004). In the present study, the c-kit expression did not correlate with the MIB-1 counts.…”
Section: Discussioncontrasting
confidence: 73%
“…Although the rate of a positive c-kit expression varied in the different studies, the rate of a positive c-kit expression of benign tumours was always lower than that of normal breast tissue and the rate of a positive c-kit expression of the breast cancer was always lower than that of benign tumours in each study (Natali et al, 1992a;Tsuura et al, 2002;Yared et al, 2004). In two studies in which the scoring method was used for the immunohistochemical staining (Chui et al, 1996;Ko et al, 2003), the immunoreactive score (IRS) of the c-kit expression of benign tumours was lower than that of normal breast tissue and the IRS of the breast cancer was significantly lower than that of the benign tumours. The finding of the c-kit expression of breast cancer is quite a contrast to the finding of EGFR and erbB2 expression of breast cancer, in which the overexpression of EGFR and erbB2 indicated a malignant phenotype of breast cancer (Tsutsui et al, 2002a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that ckit protein is present in normal breast tissue but is absent in female, but not male, breast carcinoma, 19,20 and loss of c-kit expression has been postulated as having a role in the development of breast carcinoma. 21,22 In contrast, Palmu et al 23 found that a high percentage of poor-prognosis breast cancers stain for CD-117 by immunohistochemistry. The variability in c-kit immunostaining reported in the literature most probably reflects differing sensitivities in different laboratories.…”
Section: Mast Cells In Breast Cancer S Dabiri Et Almentioning
confidence: 96%
“…In the breast, it has been found to be expressed in the normal breast ductal epithelium and myoepithelial cells, with reduced expression in benign breast lesions and carcinoma. [13][14][15][16] Previous studies that focused on carcinoma of the breast showed markedly reduced expression of c-kit in carcinoma, [13][14][15][16] borderline epithelial lesions 16 and in the breast cancer cell line MCF 7, in which c-kit was thought to mediate inhibitory signals for the growth of cancer cells in the breast. 17 In one study, however, it was found that poor prognosis cancers of the breast showed positivity for c-kit by immunostaining in the majority of the cases (82%), 18 illustrating that this issue is not yet settled.…”
Section: Discussionmentioning
confidence: 99%